The Parent and Sibling’s Support of Pediatric Cancer - Oresti, Syalvia; Elengoe, Asita (Journal of Health Sciences and Epidemiology, 2024)
A child's cancer diagnosis causes a family to experience a tremendous deal of uncertainty. Fearing what lies ahead, parents and siblings frequently worry about how therapy will impact their child's and their family's lives. Siblings and parents might feel a variety of emotions, including guilt, rage, despair, and melancholy. Siblings of ill children deal with their own psychological and emotional difficulties. The circumstances they find themselves in may cause them to feel scared, nervous, or even furious. This study aimed to describe the support provided by parents and siblings to children with cancer in West Sumatra. This research utilized a cross-sectional design and was carried out from November 2023 to March 2024 at the Childhood Cancer Care West Sumatra. The study involved 55 children, chosen using an accidental sampling method. The TEIQUE-CF instrument was employed in this research, with descriptive analysis being conducted. Approximal, 61.8% of parents and siblings are emotional about paediatric cancer. By discussing these factors, families may better prepare mentally and emotionally for this protracted and difficult journey. Children with cancer have a greater chance of making a full recovery, both mentally and physically, if they get strong support from their parents and siblings.